Atypical fibrous histiocytoma of the skull: a case report of temporal bone involvement and comprehensive literature review - Dong, Qiang; Shi, Jing; Tang, Beiyan; Wang, Hongyu; Miao, Chengliang; Ma, Yongqiang; Duan, Lei; Yuan, Guoqiang; Pan, Yawen (Frontiers in Oncology, 2026)
ObjectiveAtypical fibrous histiocytoma (AFH) is an uncommon intermediate-grade fibrohistiocytic tumor that typically arises in the dermis or superficial soft tissues. Primary involvement of the skull is exceedingly rare and poses significant diagnostic challenges. We report a rare case of primary AFH arising in the temporal bone of an adult patient and provide a focused review of previously reported skull-based cases to clarify its clinicopathologic features, diagnostic pitfalls, and management considerations.MethodsA 34-year-old man presented with progressive right-sided tinnitus and sensorineural hearing loss. Computed tomography and magnetic resonance imaging demonstrated an osteolytic temporal bone lesion with intracranial extension and compression of the adjacent temporal lobe. Gross total surgical resection was performed. Detailed histopathological evaluation and an extended immunohistochemical panel were used to establish the diagnosis. A literature review of reported skull AFH cases was conducted for comparison.ResultsHistologic examination revealed a moderately cellular spindle-cell tumor arranged in fascicles and storiform patterns, accompanied by multinucleated giant cells, hemosiderin-laden macrophages, and reactive bone formation. Immunohistochemistry showed diffuse vimentin positivity, weak cytoplasmic CD68 expression, and a Ki-67 proliferation index of approximately 20%, with negative staining for epithelial, melanocytic, neural crest, smooth muscle, and Langerhans cell markers. These findings supported the diagnosis of atypical fibrous histiocytoma. Postoperatively, tinnitus improved, while hearing loss showed limited recovery. No evidence of recurrence was observed during follow-up.ConclusionPrimary AFH of the temporal bone is an exceptionally rare entity that can mimic other destructive skull lesions on imaging and intraoperative inspection. Accurate diagnosis relies on careful histopathologic evaluation and exclusion of histologic mimickers using a comprehensive immunohistochemical panel. Complete surgical excision remains the cornerstone of treatment, and long-term follow-up is recommended due to the tumor’s intermediate malignant potential.